An exploratory of decision making factors for an overseas wedding destination : A casetudy of Indian couples, Phuket, Thailand - Nattinee McMillan (Prince of Songkla University., 2016)
Thesis (M.B.A., (Hospitality and Tourism Management (International Program))--Prince of Songkla University, 2012